Smartphone Distraction while Driving Influencing Driving Performance at FT050, Jalan Batu Pahat-Kluang - Zawawy, Nurazrin Amira; Ab. Ghani, Ahmad Raqib (Recent Trends in Civil Engineering and Built Environment, 2022)
An average of 18 people are killed on the road every day, with the number expected to rise as a result of the road user inattention error, which has been highlighted by the Malaysia Consumer Movement (MCM) [1]. With the increased usage of smartphone devices, distracted driving is assumed to be the main causes that contribute on driving performances and crash risk.  This study is conducted to investigate the influence of smartphone usage on driving performance and to identify the characteristic that influence the use of smartphone while driving. The respondent for this study are selected among residents in Kluang and Batu Pahat as they are using the federal road FT050 as their regular road. In this study, the researcher uses the quantitative and questionnaires to collect data related to influence of smartphone use while driving on driving performance and characteristic that influence the use of smartphone while driving. There were 3 sections in the questionnaire which is section A for demographic profile (5 question), section B for independent variable (11 question) and section C for dependent variable (10 question). The data collected was being analyses by using Statistical Package for Social Sciences (SPSS) version 25. The result shown that the first objectives of the study were supported, which is the most influence of smartphone usage while driving on driving performance is receive and making calls (β=0.257) and the characteristic that influence the smartphone use while driving was identified. In conclusion, this study will encourage individuals to recognize the dangers of using a smartphone while driving and be more alert.